Peran Orang Tua dalam Menghadapi Anak yang Mengalami Ketergantungan Gadget - Ainul Mardiyah; Fahri Resqi Ananda; Elfi Safina; Azka Azzahra (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Gadget dependence among children has become one of the most serious challenges in social, emotional, and academic development in the digital era. This study discusses the role of parents in addressing and managing gadget addiction in children. The approaches used include supervision, effective communication, the habituation of digital discipline, and providing examples of healthy technology use. Parents need to provide intensive guidance, set time limits for gadget use, and create alternative activities that support children’s growth and development. In addition, collaboration between families, schools, and the surrounding environment is crucial to building positive habits in gadget use. The findings indicate that consistent and educational parenting patterns can reduce the level of gadget dependence and improve children’s social, emotional, and behavioral interactions. Thus, the role of parents becomes a key factor in guiding healthy and balanced gadget use among children.